2017
DOI: 10.2147/ceor.s142239
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic outcomes of a "high-touch" clinical management program for intravenous immunoglobulin therapy

Abstract: ObjectiveTo compare clinical and economic outcomes of patients who received intravenous immunoglobulin (IVIG) therapies and were managed by a clinical management program vs the outcomes of matched controls using administrative claim data.MethodsThis retrospective cohort study used the PharMetrics Plus™ claim database between September 1, 2011 and June 30, 2014. Patients in the intervention group were from a “high-touch” IVIG clinical management program administered by a home infusion specialty pharmacy. A gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…however, the IVIg dose used is typically lower in immune deficiency states than in neuromuscular disorders. 17,52,53 Third, the lower AE rate could be the result of a shorter follow-up period in our study. The…”
Section: Descriptive Analyses Of Aesmentioning
confidence: 73%
See 2 more Smart Citations
“…however, the IVIg dose used is typically lower in immune deficiency states than in neuromuscular disorders. 17,52,53 Third, the lower AE rate could be the result of a shorter follow-up period in our study. The…”
Section: Descriptive Analyses Of Aesmentioning
confidence: 73%
“…Home administration of IVIg is cost effective because it eliminates the cost of a hospital stay or hospital outpatient infusion center visit and costs less per gram compared with hospital inpatient or outpatient settings . Analysis of the impact of site of care (place of service) on the cost of IVIg treatment has shown that home infusion patients, compared with all others, have significantly lower IVIg‐related costs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite multiple studies to try to assess outcomes in patients with PIDDs , patient outcomes of mortality and morbidity have not been fully developed for PIDDs making them more difficult still to relate to particular dosing of IgGRT. What we do know is that IgGRT is a lifesaving treatment, and it has been shown to decrease morbidity and possibly mortality in CVID , lung infections can promote bronchiectasis, noninfectious disease complications predict shortened life span and infections can impair HrQOL .…”
Section: Discussionmentioning
confidence: 99%
“…Within each autoimmune disease status category, the control group was selected from patients who were not in the program and matched 1:4 using greedy propensity score match without replacement in the PMTX + database. [20] The propensity scores were obtained by regressing the following covariates into a logistic model: age at index date, gender, patient's proximity to 102 IG treatment centers (the list of treatment centers is not included due to space limitation), four geographic regions, Charlson Comorbidity Index score,[21] and 6-month pre-index total health-care costs [Table 1]. The covariates were selected based on the interests of outcome variables through literation review and clinical judgment of our internal and external clinical experts.…”
Section: Methodsmentioning
confidence: 99%